The Role of Social Interaction in Improving the Quality of Islamic Religious Education Learning - Masykuri, Hasan Al Banna (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to investigate and understand the role of social interaction in improving the quality of Islamic Religious Education learning. This research will explore how social interactions in the classroom context can influence the effectiveness of Islamic religious learning. Apart from that, this research also aims to identify effective social interaction strategies that can be used to improve the quality of Islamic Religious Education learning in Islamic secondary schools. This research uses a qualitative approach with a case study design at Sabilurrosyad Islamic High School Malang, selecting three classes as case units (classes X, XI, and XII). Data was collected through in-depth interviews with teachers and students, as well as direct observations in classrooms to record social interactions between students and Islamic Religious Education teachers. The research location focused on classrooms at the school. The purposive sampling method was used to select research participants. The research findings indicate that instructional models such as group investigation, role-playing, and jurisprudential learning positively impact social interaction and students' understanding of PAI material. The group investigation model allows students to collaborate in identifying and exploring social and moral issues, while role-playing enables students to interact in real-life situations relevant to religious values. Furthermore, jurisprudential learning allows students to understand and integrate religious values in formulating solutions to relevant public policy issues. The role of teachers as facilitators, mentors, academic counselors, and support providers is crucial in facilitating effective social interaction in PAI classes. Support systems, including comprehensive library facilities and access to external school references, are crucial in supporting quality interactive learning. In conclusion, social interaction in the classroom significantly enhances the quality of PAI learning, and instructional approaches that encourage active interaction between students and teachers can shape a better and more accurate understanding of religious teachings.